Peningkatan Kemampuan Berbicara Berbasis Budaya Melalui Media Audio Visual Tarian Daerah - Nur Wahidah Yuliati; Siti Rochmiyati; Moh. Rusnoto Susanto; Enik Wahyuningsih (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2026)
This research aims to examine the improvement of culture-based speaking skills through the use of regional dance audio-visual media in class VI students at SDN 2 Batursari, Wonosobo. By involving 20 students as research participants, the research used a research design class action (PTK) with a qualitative approach. Data is collected through observation, tests speaking skills, and interviews with teachers and students. The results of the research show that the use of audio-visual media for regional dances is effective improve students' speaking skills. The majority of students experienced improvement in their speaking ability after the intervention, as well as gaining deeper understanding about their local culture. Student motivation and engagement in learning also increased significantly. In conclusion, the use of regional dance audio-visual media as a learning tool makes a positive contribution in improving the speaking skills of class VI students at SDN 2 Batursari, Wonosobo, while also deepening their understanding of local culture. The implications of this research are relevant for the development of culture-based education in Indonesia and countries with similar cultural contexts.